TRAJECTORYS OF DEVELOPMENT OF CONCEPTS OF REALITY - S. V. Gerasimov (Дискурс, 2018)
The article considers ideas and principles of the development of the concepts of reality, the emergence of the main ontological discourses that formed the modern space of the sphere of concepts. With the help of a consistent analysis of the systems of reality description and perception, the article attempts to elucidate the logic of the evolution of the concept of reality. The trajectory of ontological thought in the process of describing reality evolved from the connection of essences and events at the beginning of the first millennium to the most complex systems and multilevel dynamic concepts by the beginning of the 21st century. The overall goal of the study is to try to trace forming of the sphere of concepts through the concept of "reality" and "social reality", to trace the basic laws that form the concepts of reality, their identity and difference in different description systems. The article can be regarded as a preliminary consideration of a possible attempt to create a universal semantics of possible worlds, realities.